Soft Mobility Modes in Lisbon: A Descriptive Analysis of the City’s Paradigm - Martins, Jorge Miguel Nunes (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence